PERENCANAAN SISTEM INFORMASI PENGHASILAN ANGIN POMPA BAN NITROGEN BERBASIS WEB DI CV. SEKAWAN UTAMA (NITROGEN) - Mayangsari Mayangsari; Amin Sadiqin (Jurnal Bina Bangsa Ekonomika, 2022)
The Researchers write this article aims to conduct income planning analysis of the company. In the company certainly expects an increased income. So it requires a planning in improving that. The web-based calculation will be able to record in detail each time the transaction that has been ubiquitous and more efficient. The impact on these developments have been optimal for the activities in the company. Web in this study is the nitogen web which combines between nitrogen machines with web. In the web system development information planning system requires overall identification. Planning in data information system is actually not a new thing. Planning is an effort in determining various kinds of things that are about to be achieved or seven with various stages in a certain period of time. A system will have an impact on being influenced by the environment. To provide the existence of the web, there are elements supporting. Likewise, in the business field of Nitrogen tire pumps are also many developments to increase management in companies. The role of this web in a company is that it can record all transactions in detail from operating hours of operating machines not operating so it cannot anticipate cheating carried out by employees in the field.